The influence of average daily temperature and air humidity on efficiency of Helio-Cooling Absorption Bromistolithium Machines - O. S. Malinina; A. V. Baranenko; A. V. Zaytsev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The influence of changes in the average daily temperature and air humidity on the efficiency of an Absorption Bromistolithium Refrigeration Machine on solar energy for the purposes of conditioning and condensation of moisture from air is studied. The analysis of thermodynamic cycles with various circuit solutions of an Absorption Bromistolithium Refrigeration Machine is carried out. The values of the minimum temperature of the heating source are obtained, at which fresh water can be obtained for the cities of Dubai, Singapore and Chongqing